Ways of Improvement of Treatment Efficacy of Bronchopulmonary Diseases in Infants - O.G. Shadrin; S.V. Dyukareva-Bezdenezhnykh (Zaslavsky O.Yu., 2016)
The use of vitamin mineral treatment complexes for vitamin deficiency correction in infants with pneumonia is still being discussed. The paper presents the analysis of advisability of Pikovit sirupus use in children with community-acquired focal moderate pneumonia. Pikovit sirupus was found to promote to fast regression of clinical and laboratory manifestations of pneumonia. Besides the agent is a safe and effective for correction of vitamin deficiency in infants with bronchopulmonary diseases.